Intervensi Reputasi Perusahaan Pada Keputusan Pembelian: Konsekwensi Dari Influencer Instagram Dan Islamic Branding - Sulaeman, Maman; Nurhidayah, Rika; Azis, Nur; Ratnasari, Desi; Ulum, Miftahul; Wahdah, Ulya (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2024)
This study aims to analyze the influence of Instagram influencers and Islamic branding on company reputation and consumer purchase decisions. In the digital age, companies increasingly rely on influencers to build reputation and influence consumer purchase decisions, while value-based branding, especially rooted in religious principles, is becoming more popular, particularly among Muslim consumers. This research uses a survey method with a quantitative approach, where data is collected through a questionnaire distributed to 92 Rabbani product consumers. Data analysis is performed using Structural Equation Modeling (SEM) to examine the relationships between variables. The results show that Instagram influencers have a significant impact on company reputation, which in turn affects consumer purchase decisions. Islamic branding also proves to enhance company reputation, especially among Muslim consumers, which ultimately drives purchase decisions. Additionally, company reputation acts as a mediator in the relationship between Instagram influencers and purchase decisions, as well as between Islamic branding and purchase decisions. These findings indicate that companies can leverage influencers and Islamic branding to build a strong reputation and increase sales. The implications of this research highlight the importance of companies selecting the right influencers and incorporating religious values into their branding to attract consumers.